Endometrial receptivity and pregnancy outcome. (3rd July 2022) - Neykova, Konstantsa; Tosto, Valentina; Giardina, Irene; Tsibizova, Valentina; Vakrilov, Georgi
Abstract: Human implantation is a highly complex and multifactorial process. Successful implantation requires the presence of a healthy embryo, a receptive endometrium, and a synchronized molecular dialogue between the two, as well as immune tolerance/protection from the host. The endometrial receptivity refers to a hormonally limited period in which the endometrial tissue acquires a transient functional status allowing blastocyst implantation and pregnancy initiation. Global knowledge of endometrial receptivity grew up in recent years. Improvements in genetics, new biomarkers, noninvasive methods, new advanced techniques (Endometrial receptivity assay – the ERA system, proteomic analysis) offer the possibility to evaluate the endometrial status and to manage patients with infertility problems, especially women undergoing assisted reproductive treatment. This overview reports the most relevant knowledge and recent advances in the study of implantation processes from the perspective of the endometrium, often considered as being the main barrier for a successful pregnancy initiation. Endometrial receptivity is a topic of great interest and further studies are needed for the early identification of endometrial abnormalities and the discovery of new strategies for increasing the chance for the establishment of pregnancy.